Pengaruh Kompensasi dan Disiplin Kerja terhadap Produktivitas Kerja Karyawan pada PT. Idea Solusi Indonesia (Erigo) Kantor Pusat Tangerang - Muhamad Guruh; Surya Budiman; Fitri Sabina; Esti Suntari (Universitas Batanghari, 2023)
The purpose of this study was to determine whether there is a positive and significant effect between compensation and work discipline on work productivity partially or simultaneously at PT Idea Solusi Indonesia, Tangerang. This study uses an associative quantitative method where the data is in the form of a questionnaire distributed to 68 people and the data is processed using SPSS Version 22. The results of this study are the regression equation Y = 4.748 + 0.877 X1 the correlation coefficient (R) is 0.728 which means the coefficient between variable X1 to Y is strong The tcount value of the Compensation variable is 4.658 which is greater than the ttable value of 1.99656 with a significant level of 0.0 less than 0.05, it can be interpreted that Ha is accepted and H0 is rejected, so it can be concluded partially Compensation has a positive and significant effect on Productivity . the regression equation Y = 12.758 + 0.704X2 the correlation coefficient (R) is 0.721, which means the coefficient between X2 and Y is strong. The t-count value of the Work Discipline variable is 4.463, which is greater than the t-table of 1.99656 with a significant level of 0 being less than 0.05, which means that Ha is accepted and H0 is rejected. So it can be partially concluded that work discipline has a positive and significant effect on Work Productivity, the regression equation Y = 1.419 + 0.543 X1 + 0.422X2 the correlation coefficient (R) is 0.714, which means the coefficient between the variables of Compensation and Work Discipline on Very Strong Work Productivity is known. the value of the coefficient of determination (KD) = (R2) x 100% is obtained from R, namely KD = 0.640 x 100% = 64% The output is known Fcount is 57.780 and the significance value is 0 while the Ftable value is at a significance level of 0.05 with df 1 (the number of variable -1) 3-1 = 2, and df 2 (n-k-1) or = 68-2-1 = 65 obtained F table value of 3.14 So it can be concluded that Fcount > Ftable (57.780 > 3.14) and significance < 0, 05 (0 < 0.05), then Ha is accepted, so it can be concluded that Compensation and Work Discipline together affect Work Productivity.